Pengaruh Relationship Value Terhadap Word Of Mouth (Wom) (Studi Pada Konsumen Pesan Antar Rumah Makan Spesial Sambal Di Kota Tangerang) - Sam Sofilo Sinaga; I Made Sukresna (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to directly examine the effect of relationship value, satisfaction, trust, and commitment, on the consumer's Word Of Mouth (WOM) (a study on consumers ordering spesial sambal (SS) in the city of Tangerang). The population in this study were all customers who made purchases by ordering between special chili sauce (SS) restaurants in the city of Tangerang. The sample method used in this research is purposive sampling. Data analysis used confirmatory factor analysis, validity and reliability tests, and structural equation modeling (SEM). using 100 respondents. The results of the study indicate that this finding recommends special chili sauce (SS) restaurants to continue to increase the value of relationships, satisfaction, trust, and commitment as a consideration in selling their products so that consumers more talk about their product or Word Of Mouth (WOM). These factors have the potential to increase consumers to actively use delivery services and discuss their products with other consumers.